Pengembangan Lembar Kerja Peserta Didik (LKPD) Laju Reaksi Berbasis Inkuiri Terstruktur Kelas XI SMA - Rosi Efliana; Minda Azhar (Universitas Negeri Padang, 2019)
Learner Worksheet (LKPD) of reaction rates based structured inquiry in class XI SMA had been dertemine validity and practicality. The type of research used is Research and Development (R and D). The development model was a 4-D model consisting of 4 stages, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate. The disseminate stage was not carried out due to time and cost constraints. The research instrument used was a questionnaire validation and practicality questionnaire. The validation questionnaire was filled by 3 chemistry lecturers from FMIPA UNP and 2 chemistry teachers from SMAN 2 Lubuk Basung. Practicality questionnaire was filled by 2 chemistry teachers and 30 students of class XII MIPA 3 SMAN 2 Lubuk Basung. Data were analyzed using kappa moments. The average kappa moment of validity test was 0.87 with a very high validity category. The average kappa moment of teacher were 0,88 with a very high practicality category. The average kappa moment of student were 0,87 with a very high practicality category. Thus, it was concluded that reaction rates LKPD based on structured inquiry was valid and practice.